2018
DOI: 10.12681/mms.18099
|View full text |Cite
|
Sign up to set email alerts
|

New Mediterranean Biodiversity Records (July 2018)

Abstract: In the present article, new records are given for 15 species (4 native and 9 alien and 2 cryptogenic), belonging to 6 Phyla (i.e. Chlorophyta, Ctenophora, Cnidaria, Mollusca, Arthropoda, and Chordata), from 10 Mediterranean countries: Morocco: the finding of the crab Callinectes sapidus represents the westernmost one of the species in the Mediterranean; Italy: first records of the nudibranch Polycera hedgpethi from the harbour of La Spezia, and first finding of the invasive ctenophore Mnemiopsis leidyi in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Looking at the whole Mediterranean Sea, the Atlantic blue crab is almost ubiquitous in Aegean and Levantine basins and in the last two decades has become common along the Ionian coasts as well as in the Adriatic Sea, with repeated observations in Italy, Croatia, Montenegro, and Albania (Mancinelli et al 2017b). In the last years, increasing records of blue crab have also occurred in Sardinian waters as reported by Piras et al (2019) and in the North-East of the Iberian Peninsula by Fuentes et al (2019), in Algeria by Benabdi et al (2019), in Morocco by Oussellam and Hocein (Chartosia et al 2018) and South-west Sicily (Lipej et al 2018 and present records), suggesting that the species continues its expansion in the western sector of Mediterranean basin (Fig. 2).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Looking at the whole Mediterranean Sea, the Atlantic blue crab is almost ubiquitous in Aegean and Levantine basins and in the last two decades has become common along the Ionian coasts as well as in the Adriatic Sea, with repeated observations in Italy, Croatia, Montenegro, and Albania (Mancinelli et al 2017b). In the last years, increasing records of blue crab have also occurred in Sardinian waters as reported by Piras et al (2019) and in the North-East of the Iberian Peninsula by Fuentes et al (2019), in Algeria by Benabdi et al (2019), in Morocco by Oussellam and Hocein (Chartosia et al 2018) and South-west Sicily (Lipej et al 2018 and present records), suggesting that the species continues its expansion in the western sector of Mediterranean basin (Fig. 2).…”
Section: Resultssupporting
confidence: 71%
“…3 Species presence records map of Callinectes sapidus in the Mediterranean basin. Red star (present study); green triangle (Culurgioni et al, 2020); blue asterisk (Benabdi et al, 2019); dark green triangle (Fuentes et al, 2019); red asterisk (Munari & Mistri, 2019); orange triangle (Piras et al, 2019); fuchsia triangle (Labrune et al, 2019); black asterisk (Chartosia et al, 2018), green asterisk (Garcia et al, 2018); light orange asterisk (Lipej et al, 2018); yellow circle (Mancinelli et al, 2017); blue triangle (Froglia, 2017) and light blue triangle (https://www.pole-lagunes.org) manuscript. All authors participated and commented in various aspects of discussing the results to achieve the final manuscript.…”
Section: Discussionmentioning
confidence: 75%
“…Caulerpa taxifolia var. distichophylla, reported for the first time in the Mediterranean Sea in 2006 from the south coast of Turkey, was subsequently reported from Sicily, Cyprus, Malta, Greece, Libya, Lebanon, Syria and Tunisia (Verlaque et al, 2015;Chartosia et al, 2018). In the current paper we report the taxon from Algeria.…”
Section: Caulerpa Taxifolia Var Distichophylla (Sonder) Verlaque Humentioning
confidence: 53%
“…This new scyphozomedusa was initially determined as Pelagia benovici (Piraino et al, 2014) and later recognized as new genus Mawia benovici (Avian et al, 2016). Recently Chartosia et al (2018) reported the presence of Pelagia benovici (alternate representation of Mawia benovici) in the Ioanian Sea. The photos of the specimens published in this paper by Anastasiadis and Piraino show some characters of Mawia (in particular horseshoe shaped gonads and colourless tentacles) even if we never observed the same transparency of umbrella in the specimens from the Adriatic (which in our living samples presented always an umbrellar colour brown) and other characters closer to Pelagia genus (oral arms with evident nematocyst warts and solid mesogleal axis).…”
Section: Further Sightings Of Mawia Benovici In the Adriatic Seamentioning
confidence: 99%